Evaluación de eichhornia crassipes (mart.) Solms. Y lemna minor (l.) Griff. Como potenciales especies fitorremediadoras, de aguas contaminadas a causa del faenamiento de ganado vacuno y porcino del camal municipal ubicado en el barrio la recta, cantón el Pangui - Pineda Cuenca, Leoncio Alberto (2016)
This research was carried out next to the installations of the Municipal slaughtering house; town “El Pangui”, which is located in “La Recta” neighborhood from the same town, the purpose was to test the grade of sewage water generated by the activities of slaughter, using the species Eichhornia crassipes and Lemna minor. The development of the project was first to develop a characterization to determine the grade of pollution of the sewage water from slaughtering house through a laboratory analysis of the physical and chemical characteristics, immediately it was determined the flow that is generated daily through the volumetric method. After, it was built five experimental pools of reinforced concrete each one of 0.7m3, in the first two pools a total of 36 plants (18 plants in each pool) of the species Eichhornia crassipes were planted, while in the following two pools an amount of 150 grams (75gr. Each pool) of the species Lemna minor were planted. In which was entered a representative flow (0.02 lts / sg) of the total sewage water generated by the slaughtering house. The time set for the research process was three months. To determine the removal efficiency of the pollutants, a laboratory analysis was carried out, achieving a reduction of SST (99.6%), chlorides (85.8%), oils and greases (98.9%), DBO (98, 4%) and DQO (95.8%), all of these with Eichhornia crassipes specie. Finally, a surface flow wetland was designed with the help of the AUTOCAD software, taking into account the species that presented the highest percentage of removal pollutants.